Deceit and Denial : The Deadly Politics of Industrial Pollution - GERALD MARKOWITZ , DAVID ROSNER (University of California, 2013)
This is the sixth of the California/Milbank Books on Health and the Public. The publishing partnership between the Fund and the Press seeks to encourage the synthesis and communication of findings from research that could contribute to more effective health policy. Gerald Markowitz and David Rosner demonstrate the significance for policy of the methods and findings of historical scholarship. On the basis of research that has been reviewed by experts in history, biomedical science, and policy, they describe decisions by executives of corporations that produce lead products and plastics to withhold information about the health hazards of their products and production processes from their employees and regulators. These decisions contributed to the severe illness and death of many employees of these corporations as well as of persons who lived in the wrong place at the wrong time.